2022
DOI: 10.1097/icl.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Reasons for the Discontinuation of Orthokeratology Lens Use: A 4-Year Retrospective Study

Abstract: Purpose:Although orthokeratology has a positive effect on myopia control, some patients discontinue orthokeratology lens use. This study analyzed the data of all patients who had been fitted with an orthokeratology lens in the past 4 years and the reasons for discontinued lens use, with the aim of improving the prevention and control of myopia.Methods:This retrospective study analyzed the data of patients, aged 8 to 18 years, fitted with orthokeratology lenses from 2017 to 2020. The ametropic spherical lens po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In order to prevent and control childhood myopia, orthokeratology (OK) lenses have attracted increasing attention from ophthalmologists and myopic patients because of their good corrective effects and ability to control myopia progression. After more than 30 years of clinical application, the effectiveness of OK lenses in controlling myopia has been confirmed [ 41 ]. Studies have shown that compared to single-vision glasses and contact lenses, the inhibitory effect on axial elongation over 2 years ranges from 32 % to 63 % [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent and control childhood myopia, orthokeratology (OK) lenses have attracted increasing attention from ophthalmologists and myopic patients because of their good corrective effects and ability to control myopia progression. After more than 30 years of clinical application, the effectiveness of OK lenses in controlling myopia has been confirmed [ 41 ]. Studies have shown that compared to single-vision glasses and contact lenses, the inhibitory effect on axial elongation over 2 years ranges from 32 % to 63 % [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This dropout rate is consistent with other types of lenses, signifying the comparable discontinuation rates [ 5 , 49 ]. Lina Ma’s extensive 4-year study of 2499 patients reported 50 cases of lens discontinuation, which were attributed to nonadherence (50%), insufficient sleep (18.0%), financial constraints (16.0%), limited effectiveness (10.0%), and corneal infiltrates (6.0%) [ 50 ]. Importantly, there were no significant differences in the causes of discontinuation among the different age groups or genders.…”
Section: Discussionmentioning
confidence: 99%
“…After more than 30 years of clinical use, it has been proven that OK lenses signi cantly reduce myopia [19] . Many patients and their families have agreed that using these lenses for acceptable therapy is acceptable because they may be worn at night and yet provide excellent vision during the day.…”
Section: Discussionmentioning
confidence: 99%